Manifestation of moderation in the context of Islamic Law: Maqasid study - Muhammad Husni, Ahmad; Busari, Saheed Abdullahi; Muhammad Husni, Amin (Al Hikmah Research & Publication Centre, 2022)
The study discusses an optimal method for building moderate society through the higher objective of Shariah, by employing the five essentials of goals of Islamic law based on the God Almighty command to His servants on righteousness, moderation and forbade them from excesses and corruptions. Islamic law prohibits extremism, intolerance, and extremism while it promotes respect among different cultural, religious, and civilization pluralism, and on the other hand, it renounces racism. The permissive people describe adherents of religion and moderation as hardliners, fanatics, and extremists against modern developments because of the permissive view that pornography contents should be permissible in religion as means of moral and civilization progress. They also claim that strict adherence to religious obligations leads to a lack of freedoms and compliance with global civilization. To this effect, Shariah law presents the ideal and best model for social organization and best human behavior practices, so that they may live a good and contented life, in harmony with the nature that God created people with. The study employs analytical induction methods with a basis for addressing contemporary issues and Islamic thought. It also discusses the higher objectives of Shariah from several angles and at the forefront explicates the criterion and judgment. Despite the setbacks and challenges confronting the Islamic nation, Allah has destined goodness and empowerment for its sustainability and never seizes to exist. The study concluded that achieving this requires: First: adherence to the highest revelation and most trusted bond of religion and strengthening loyalty to the Islamic faith and law. Second: The necessity of gathering the efforts of the Muslim community members and mobilizing the scholarly, intellectual, youth, and women forces. Third: Knowing the deficiency and resolving to address them through the higher objectives of Shariah, then hopefully Allah destines triumph after refraction, and victory after defeat.